DIGITAL MARKETING ASSISTANCE AND BUSINESS LEGALITY AT MSME MBOK KARTI CATERING - Selamet Eko Budi Santoso; Shelomita Candra Herdiana (Universitas Muhammadiyah Purwokerto, 2023)
A small business called MSMEs Mbok Karti Catering specializes in creating a variety of cakes for meetings and other events. However, this business faces several obstacles. Firstly, they have limited reach when it comes to distributing and marketing their products, which limits their ability to serve a larger area. Additionally, they do not currently possess a business license, which further hinders their marketing efforts. To address these challenges, a service team has stepped in to provide assistance with digital marketing and help the business obtain the necessary licenses. Thanks to this support, Mbok Karti Catering's products can now be marketed directly through social media and the business now has a complete license. As a result, Mbok Karti MSMEs have been able to increase their product sales and improve their overall turnover. Keywords: SMEs, digital marketing, business legality